Overview of Body Mass Index and Blood Pressure of Medical Science Faculty Student in Prima Indonesia University, 2017 - Fautia Ristina; Wienaldi (Britain International for Academic Research (BIAR) Publisher, 2021)
The aims of this study discussed overview of body mass index and blood pleasure in Medical Science Faculty Student. This research is a descriptive study with a cross-sectional study design, namely how to approach, observe or collect data at the same time 10. Based on the research results, it was found that the majority of BMI students from the Faculty of Medicine UNPRI Medan class 2017 were normal, namely 64 people (64.6%), then followed by students with an overweight BMI of 29 people (29.3%), underweight and obese respectively. only 3 people (3.0%). Based on the results of the study, it was found that the majority of the blood pressure of the 2017 UNPRI Medan Faculty of Medicine students was completely normal (100%).